SC-FDM-IDMA Scheme Employing BCH Coding - Roopali Agarwal; Manoj K. Shukla (International Journal of Electrical and Computer Engineering (IJECE), 2017)
In OFDM-IDMA scheme, intersymbol interference (ISI) is resolved by the OFDM layer and multiple access interference (MAI) is suppressed by the IDMA layer at low cost . However OFDM-IDMA scheme suffers high peak-to-average power ratio (PAPR) problem. For removing high PAPR problem a hybrid multiple access scheme SC-FDM-IDMA has been proposed. In this paper, bit error rate (BER) performance comparison of SC-FDM-IDMA scheme, OFDM-IDMA scheme and IDMA scheme have been duly presented.  Moreover, the BER performance of various subcarrier mapping methods for SC-FDM-IDMA scheme as well as other results with variation of different parameters have also been demonstrated. Finally simulation result for BER performance improvement has been shown employing BCH code. All the simulation results demonstrate the suitability of SC-FDM-IDMA scheme for wireless communication under AWGN channel environment.